SCHOOL CULTURE SEBAGAI TINDAKAN PREVENTIF DAN SOLUTIF DALAM MANAJEMEN KONFLIK DI SMK DARUL KAROMAH SINGOSARI - M Kholilulloh (STAI Ma'had Aly Al-Hikam Malang, 2020)
In management studies, the presence of educational conflicts cannot be separated from the daily problems felt by managers of educational institutions. This conflict occurs because the school is a gathering place for a variety of complex characteristics and characteristics, which meet with interactions within the school environment. SMK Darul Karomah is one of the vocational schools in the Randuagung area, Singosari, Malang which has good conflict management. This SMK is different from schools in general, where this school has certain steps or strategies in overcoming and preventing conflicts among students, or conflicts that occur inside or outside the school. One of the conflict management strategies contained in SMK Darul Karomah is the existence of School Culture.Based on the cases taken, the formulation of the research problem is to describe how the form of school culture at SMK Darul Karomah and to describe how school culture is a preventive and solution action in conflict management at SMK Darul Karomah. In this study, the method used is qualitative research located at SMK Darul Karomah Randuagung. The data collection techniques used were observation, interviews and documentation. Data analysis was carried out by collecting data which was then selected and simplified according to research findings, by presenting data that could be drawn conclusions. The data validity checking techniques used by the author in this study include: credibility, transfrability, independence, and confirmability.The results of this study can be concluded that: 1) school culture at SMK Darul Karomah has a pesantrenan nuance, there are daily, weekly, monthly and annual activities considering that this vocational school is in the middle of Darul Karomah Islamic boarding school. 2) school culture as a preventive and solution action in conflict management at SMK Darul Karomah in the form of cultivating habits, ishlah, tabayyun and punishment with pesantren nuances.